An High Equipped Power Constrained Algorithm For OLEDS Based On MSR (International Journal of Engineering and Computer Science, 2018)
This paper presents a power-constrained contrast enhancement algorithmic program for organic semiconductor diode display based on multi scale retinex (MSR). In general, MSR, that is the key element of the planned algorithmic program, consists of power controllable log operation and sub band wise gain management. First, we decompose associate input image to MSRs of various sub-bands, and figure a correct gain for every MSR. Second, we have a tendency to apply a coarse-to-fine power management mechanism, that re computes the MSRs and gains. This step iterates till the target power saving is accurately accomplished. With video sequences, the contrast levels of adjacent pictures are determined systematically using temporal coherence so as to avoid unsteady artifacts. Finally, we gift many improvement skills for data processing. Experimental results show that the planned algorithmic program provides better visual quality than previous strategies, and a consistent power-saving magnitude relation while not unsteady artifacts, even for video sequences